66 A NOVEL APPROACH FOR PROVIDING NURSING HOME RESIDENTS WITH THEIR VITAMIN D REQUIREMENT. (1st March 2005) - Holick, M. F.; Mathieu, J.; Ingersoll, D.; Chen, T.
Abstract : It is now recognized that vitamin D deficiency is epidemic in nursing home residents. The consequences are the development of osteoporosis and the painful bone disease osteomalacia. In addition, vitamin deficiency increases muscle weakness and sway and therefore increases risk of falling and hip fracture. It is well documented that a multivitamin containing 400 IU of vitamin D and a dietary intake of vitamin D are not adequate to satisfy nursing home residents vitamin D requirement. We have designed a lighting system that emits high flux of ultraviolet B radiation (UVB) (290-315 nm) which is responsible for producing vitamin D3 in the skin (10). Healthy adult volunteers of skin types 2, 3 and 4 were recruited. They were exposed to the UV light system, which measured 6 ft in height and 3 ft in width. Wearing a bathing suit and protective eye goggles the volunteers were exposed to 50-120 seconds on the front and then back of their bodies 3 times a week for one month. After one month subjects with skin types 2, 3 and 4 had an increase in their circulating concentration of 25(OH)D by at least 25% and in some subjects as much as 100%. These preliminary results suggest a simple and effective lighting system can be developed and installed in nursing homes that can be effective in preventing vitamin D deficiency in nursing home residents.